TENTANG “ IMPLEMENTASI PROGRAM SIRANCAK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PADANG DALAM MENINGKATKAN LAYANAN BERBASIS DIGITAL” - Mutiara Ramadhani; Syamsir Syamsir; Bulan Shakira Efendy; Clarissa Amanda; Olivia Dwi Ruselda (Jurnal of Management and Social Sciences, 2023)
The waste bank is a container that can solve the problems that the community is currently experiencing through a program by utilizing dry waste to sort and having management like banking but what is stored is waste. The management of the Pancadaya Kuranji Garbage Bank, Padang City, has used many ways to change people's environmental care behavior. The focus of this research is to find an overview of waste bank management efforts, including: knowing the implementation, obstacles, and efforts made in overcoming obstacles to implementing the garbage bank application. in realizing pancadaya good governance in Kuranji, Padang city. This study uses a qualitative approach with data collection techniques of observation, interviews, and documentation studies. The discussion of this research is based on data from interviews with secretaries, coordinators, and members at the Pancadaya Kuranji Garbage Bank, Padang City. The theoretical studies used are Good governance, E-Government, Aspects of Digital Governance, The Role of Digital Governance in realizing good governance, Garbage Bank , and the Garbage Bank Application. The results of this study indicate that the Pancadaya Garbage Bank Application has not been able to provide maximum service. Because the application features are not related to service to the community, and data processing of people who carry out waste transactions. In terms of limited facilities and infrastructure, the solution is in the form of government policy to embrace the private sector in the form of integrated cooperation which certainly benefits both parties.